O adaptacji filmowej opowiadania Zofii Nałkowskiej "Przy torze kolejowym" - Jazdon, Mikołaj (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2009)
About the Film Adaptation of Zofia Nałkowska’ short story “Aside of the Railway” Andrzej Brzozowski directed a live action short subject based on Zofia Nałkowska’s short story Aside of the Railway in 1963. The film was banned by the communist authorities and presented for the first time as late as in 1992. This is a story of runaway Jewish woman who jumped out of a train aiming at a concentration camp somewhere inPoland occupied by he Nazis. With a heavily wounded knee she lies aside of the railway looking at Polish countrymen who gathered near her and see no chance to help her as they fear of the Nazis. When she ask them not to carry her to Germans’ one of the onlookers shots her on the spot. Brzozowski made numerous modifications to present the tragic situation from the short story in film. One of them is the change of the point of view. In film it is the POV of the wounded woman, when in the short story it is presented by a witness who told the writer about the events only after the war. Brzozowski also changed the time of events from spring in the story to snowy winter in the film and focused on two main characters – the Jewish woman and the man who seemed most determined to help her and shot her in the end.